Factors Associated with the Menstrual Cycle Student Public High School 12 in Maros - Zuriati, Zuriati (PT.Mantaya Idea Batara, 2021)
Menarche that occurs in young women in the world today is closely related to the factors that influence. decreased age of menarche associated with nutritional status in adolescents. The goal to know the relationship of menarche with nutritional status in adolescents in SMP Negeri 2 Bolaang.